Penguatan Personal Branding Mahasiswa Teknologi Pendidikan UPI melalui CV Berbahasa Indonesia di cvmaker.co.id - Ghani Razaqa Mahaputra; Farrel Zahran Rabbani; Rafly Rizky Fauzi; Muhammad Tomas Umar Sebastian (Lembaga Pengembangan Kinerja Dosen, 2025)
Enhancing personal branding is a crucial factor in building students' academic and professional careers. One way to strengthen personal branding is by creating an attractive and professional Curriculum Vitae (CV). This study aims to improve the skills of Universitas Pendidikan Indonesia students in drafting CVs in Indonesian using the digital platform cvmaker.co.id. This activity is designed to provide practical understanding in composing a CV that effectively reflects students' competencies and personalities. The method used is technology-based direct training, involving students in each stage of CV creation, from personal data collection to the final design. The expected outcome is an improvement in the quality of students' CVs, which can enhance their personal branding and increase opportunities in both academic and professional fields.